91.6k views
2 votes
I need help fast! This is polynomials help

I need help fast! This is polynomials help-example-1
User Paulkmoore
by
5.6k points

1 Answer

3 votes

Answer:

  • incorrect
  • correct
  • incorrect

Explanation:

A + B = (-4x^2 +2x -5) +(3x^2 +6) = x^2(-4+3) +x(2) +(-5+6) = -x^2 +2x +1

The given sum is Incorrect.

__

A - C = (-4x^2 +2x -5) -(-5x -4) = -4x^2 +x(2+5) +(-5+4) = -4x^2 +7x -1

The given difference is Correct.

__

B + C = (3x^2 +6) +(-5x -4) = 3x^2 -6x +2

The given sum is Incorrect.

User Jowett
by
6.4k points